Evaluation of inhalation technique of community pharmacists - focus on dry powder inhalers - Jovanović, Marija; Roganović, Maša; Kovačević, Milena; Ćulafić, Milica; Vučićević, Katarina; Vezmar Kovačević, Sandra; Milenković, Branislava; Miljković, Branislava (Archives of Pharmacy, 2022)
Treatment of asthma and chronic obstructive pulmonary disease (COPD) requires optimal use of inhalers. Pharmacists have a significant role in educating patients on the correct use of inhalers, including dry powder inhalers (DPI). The aim of the study was to assess and compare pharmacists’ DPI technique demonstration skills before and after the education. The study included only pharmacists without previous training for correct use of inhalers. Pharmacists’ score was assessed at baseline and after the training of the correct use of 5 types of DPI. The participants were given a 1-point score for each of four steps performed correctly. Statistical analysis was performed using the SPSS program (version 25). Wilcoxon test was used for score comparison before and after education. The mean score after training was 3.8±0.57 for all types of DPI. There was a statistically significant difference (p<0.05) in achieved scores before and after pharmacists’ training taking into account 594 comparisons. In 575 cases the score was higher after training, in only 2 cases the score was lower, while in 17 cases it was even. The total error rate for first step (device preparation) was 2.86%, for second step (expiration) it was 4.71%, for third step (inhalation) it was 6.73% and for last step (holding breath) it was 5.56%. The results imply that training improved pharmacist skills regarding the DPI technique. It may contribute to better control of asthma and COPD, after education of patients. This is especially important considering that pharmacist are the most accessible health care professionals.